Property Criminal Sanctions as a Instrument of the Prevention of Crime Against Property - Jovašević, Dragan (Kriminalističke teme, 2004)
In this paper the author analysed theoretical and practical aspects about prescribing, passing and executing to property criminal sanctions in criminal law of Serbia and Montenegro: 1) punishments (fine and confiscation) and 2) measure of safety (appropriation of thing). These sanctions have repressive and special preventive separately when the. court is passing these criminal sanctions against executors of property criminal offences. The preventive character these sanctions result from two characterisctics about property criminal offences: 1) these offences have resulted self-interest or intention of illegal unlawfull appropriation property employment and 2) executor or other person has acquired illegal unlawfull property employment. Because the property criminal offences are the most numerous of the criminal offences in all modern law systems, the property criminal sanction have special, unstimulate and important role in keeping down and prevention these criminal offences.